Analisis Kestabilan Lereng pada Perencanaan Pembangunan Tanggul Kali Semarang, Jawa Tengah - Pradana, Bayu Arga (Geological Engineering E-Journal, 2013)
Indonesia is a mostly country who have a mass movement disasters. These disasters are common in many areas, especially during the rainy season. This study aims to determine the safety factor of the slope value at the location so it can be seen from geotechnical reconstruction methods necessary for planning the construction of the embankment will be done on one time, Semarang.The research method used is descriptive and experimental methods. Slope stability analyzes performed using computational methods using software GeoStudio 2007, which then conducted an experimental method to simulate the value of cohesion on improving safety factor (Fs).From field observations and analytical results, the type of ground motion that can occur in the form of research creep, which is triggered by the huge burden of the activities of the local community and the load of the Kali Semarang have a large discharge and high during the rainy season.Based on the analysis of slope stability, slope conditions has a value of 0.809 with a safety factor of cohesion to the clayley sand layer 5.89 kPa and 8.92 kPa in clay layer. The simulation results obtained are a great value for the safety factor (Fs) 1.786 where the results are worth the value of cohesion at 15.89 kPa clayley sand and the clay has a cohesion value of 18.92 kPa, indicating that the slope is said to be secure and stable against mass movement must have increased the value of Â± 10 kPa cohesion. Grouting method is an effective method to increase the value of cohesion in the rock formâs.In planning the embankment to be performed on site execution of the research required cutting slopes up to Â± 90 Â°, the situation is then carried out two ground reinforcement methods that do the grouting method to increase the value of cohesion so that the constituent rocks have a high carrying capacity, and the execution of the sheetpile installation method will make retaining wall at the edge of the Kali Semarang make it strong andout construction of safe and effective.